2022
DOI: 10.3390/membranes12040419
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Water and Methanol Dynamics in Sulfonated Polyether Ether Ketone Nanocomposite Membranes Bearing Layered Double Hydroxides

Abstract: Conventional Nafion membranes demonstrate a strong affinity for methanol, resulting in a high fuel crossover, poor mechanical stability, and thus poor performance in direct methanol fuel cells (DMFCs). This study involves the synthesis and physiochemical characterization of an alternative polymer electrolyte membrane for DMFCs based on sulfonated poly(ether ether ketone) and a layered double hydroxide (LDH) material. Nanocomposite membranes (sPL), with filler loading ranging between 1 wt% and 5 wt%, were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…All the nanocomposite membranes were prepared by simple solution intercalation method [ 51 , 54 , 55 , 56 ]. In the case of Nafion/LDH composite membrane, 1 g of commercial Nafion resin solution was heated at 60 °C until dried from the solvents and then re-dissolved in 10 mL of DMF until a clear solution was obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the nanocomposite membranes were prepared by simple solution intercalation method [ 51 , 54 , 55 , 56 ]. In the case of Nafion/LDH composite membrane, 1 g of commercial Nafion resin solution was heated at 60 °C until dried from the solvents and then re-dissolved in 10 mL of DMF until a clear solution was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…According to the literature, 3 wt.% of loading has been demonstrated to be the optimal one in most of the nanocomposite systems and for various types of inorganic materials [ 45 , 46 , 47 , 48 , 49 ]. Additionally, during our previous works, we have demonstrated that the introduction of 3 wt.% of LDH material can ensure the maximum improvement in terms of transport properties, conductivity values, and mechanical properties either in the case of Nafion-based [ 50 ], sPEEK-based [ 51 ], and sPSU-based [ 46 ] composite membranes. Indeed, higher filler contents resulted in particle agglomeration, membrane inhomogeneity, and thus deterioration of the physicochemical and electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, a different NMR tube containing an sPSU or sPL sample was placed in the probe and analyzed. This allowed for a more rapid evaluation of how the nanoconfinement effect and interaction with the functional groups of both the polymer and the filler particles affect the chemical shift of water molecules [ 55 , 56 ]. Signal deconvolution was carried out using Origin Software, and details on mathematical model are provided in the SI.…”
Section: Methodsmentioning
confidence: 99%